2009
DOI: 10.1029/2008jd010825
|View full text |Cite
|
Sign up to set email alerts
|

Stable water isotopes in HadCM3: Isotopic signature of El Niño–Southern Oscillation and the tropical amount effect

Abstract: [1] Stable water isotopes have been added to the full hydrological cycle of the Hadley Centre Climate model (HadCM3) coupled atmosphere-ocean GCM. Simulations of d 18O in precipitation and at the ocean surface compare well with observations for the present-day climate. The model has been used to investigate the isotopic anomalies associated with ENSO; it is found that the anomalous d

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
225
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(230 citation statements)
references
References 65 publications
4
225
0
1
Order By: Relevance
“…This makes comparison of climate model output with the proxy data non-trivial. The most straightforward comparison with the measured data would be to include models of the proxies within the climate model, but such models are not present in this version of FAMOUS (although the oxygen isotope scheme of Tindall et al (2009) has now been implemented for future use).…”
Section: Comparisons With Climate Proxiesmentioning
confidence: 99%
“…This makes comparison of climate model output with the proxy data non-trivial. The most straightforward comparison with the measured data would be to include models of the proxies within the climate model, but such models are not present in this version of FAMOUS (although the oxygen isotope scheme of Tindall et al (2009) has now been implemented for future use).…”
Section: Comparisons With Climate Proxiesmentioning
confidence: 99%
“…A number of studies have clearly demonstrated their usefulness for an improved climatic interpretation of present and past water isotope variability (e.g. Jouzel et al, 2000;Mathieu et al, 2002;Noone and Simmonds, 2002;Werner and Heimann, 2002;Vuille and Werner, 2005;Lee and Fung, 2008;Tindall et al, 2009;Risi et al, 2010b). A comparison of different models allows for the evaluation of robust features, and the ability to scrutinize each model's parametrizations.…”
Section: Introductionmentioning
confidence: 99%
“…Today, most IPCC class AGCMs include the possibility for water isotopes tracing (Hoffmann et al, 1998;Noone and Simmonds, 2002;Mathieu et al, 2002;Lee et al, 2007;Yoshimura et al, 2008;Risi et al, 2010;Werner et al, 2011). The subsequent development of water isotopes modules in oceanic general circulation models (OGCM) (Schmidt, 1998;Delaygue et al, 2000;Xu et al, 2012) opens the prospect for coupled simulations of present and past climates, conserving water isotopes through the hydrosphere (Schmidt et al, 2007;Zhou et al, 2008;Tindall et al, 2009). In general, general circulation models (GCMs) have been used exclusively to simulate separately water isotopes in the atmosphere and ocean components.…”
Section: Introductionmentioning
confidence: 99%